Prevention of IOL Laser Damage after YAG Laser Destruction in Children with Secondary Cataract - N. N. Arestova; N. S. Egiyan; T. B. Kruglova; R. V. Kalinichenko (Oftalʹmologiâ, 2021)
Background. In recent years there is a tendency to more often admission in our institution children with multiple IOL damage caused by laser treatment of secondary cataract operated at local hospitals.Purpose. To analyze the causes of laser damage to IOL in children underwent YAG laser destruction of secondary cataract and find best ways to prevent them.Patients and methods. We analyzed the frequency of acrylic IOL damage after YAG-laser destruction in 593 children with congenital, posttraumatic and postuveal cataract at age from 6 months to 17 years (one third of patients were less than 3 years old). All laser operations were performed on identical YAG-laser, by the same protocol and by one surgeon.Results. We confirmed that main reliable prevention factor of damage to IOL in children is the precise focus of laser beam. In past 10 years in our institution, we managed to decrease frequency of laser damage to IOL in children with secondary cataract in 4.5 times due to performing operations under general anesthesia (43.8 % in 2007–2008, 65.8 % in 2018). Thus, decreasing frequency from 5.9 % to 1.3 % in the same age group of patients.Conclusion. To achieve the effective prevention of laser damage to IOL in cases of YAG laser destruction of secondary cataract it is essential to use general anesthesia in following conditions: children 5 or below age, non-contact children of older age, children with nystagmus, CNS pathology, psychomotor development delay. It is unacceptable to perform this operations without general anesthesia in children that can’t fix the gaze. Furthermore it is important to use contact lenses to fix the eyes of a child, select the individual less invasive method and technique of laser operation, utilize single short impulses with minimal effective energy, thoroughly follow standard safe energy modes (impulse energy shouldn’t be more than 2.4 mJ, impulse number should be not more than 100).